2015
DOI: 10.1016/j.sna.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

An inverse Prandtl–Ishlinskii model based decoupling control methodology for a 3-DOF flexure-based mechanism

Abstract: Copies of full items can be used for personal research or study, educational, or not-forprofit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. Abstract : A modified Prandtl-Ishlinskii (P-I) hysteresis model is developed to form the feedforward controller for a 3-DOF flexure-based mechanism. To improve the control accuracy of the P-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…[11][12][13] Among these hysteresis models, the P-I model has been widely utilized due to the simple structure, easy modeling identification, and analytical inverse. 14 Ang et al observed that the hysteresis slope of the PEA was affected linearly by the actuation rate, and they accordingly designed a rate-dependent P-I (RDPI) hysteresis slope model. 15 Qin et al established a novel direct inverse modeling approach to directly obtain the inverse P-I model based on experimental data.…”
Section: Article Scitationorg/journal/rsimentioning
confidence: 99%
“…[11][12][13] Among these hysteresis models, the P-I model has been widely utilized due to the simple structure, easy modeling identification, and analytical inverse. 14 Ang et al observed that the hysteresis slope of the PEA was affected linearly by the actuation rate, and they accordingly designed a rate-dependent P-I (RDPI) hysteresis slope model. 15 Qin et al established a novel direct inverse modeling approach to directly obtain the inverse P-I model based on experimental data.…”
Section: Article Scitationorg/journal/rsimentioning
confidence: 99%
“…This method does not require complicated modeling of thermo-mechanical parameters, and the method only considers the output of the actuator corresponding to the applied input. 7,8 Different models have been proposed to characterize the hysteresis and nonlinearities of smart materials at a single-frequency such as Krasnoselskii-Pokrovskii (KP), Preisach, and Prandtl-Ishlinskii (PI) models. 9 Among these models, PI is more popular in model-based control systems because of its simplicity and analytical inverse.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on how to improve the accuracy of the nanopositioning stage by improving the traditional PI model. There are ways to change the operator by modifying the classical PI model into a generalized PI model, resetting the initial value that can eliminate the influence of the polarization by changing the hysteresis characteristics of the symmetric bias modeling and piecewise fitting method [20][21][22][23]. The above researches greatly improve the hysteresis description accuracy of the nanopositioning stage for single-ring linear voltage.…”
Section: Introductionmentioning
confidence: 99%